Child-rearing practices in thirty Fukienese families in greater Manila and implications for education - Barber, Wanda Louise 1928- (s.n.], 1967)
Certain areas of the Fukienese child-rearing practices are explored in this study to determine their relevance to education. Specifically, this study exposed the child-rearing practices of the Fukienese in Greater Manila with respect to pre- and post-natal practices, nurturance and discipline, the current practices related to schooling in this group, and the educational implications of these child-rearing practices and related beliefs.